PERSEPSI SISWA LEMBAGA PENDIDIKAN MENENGAH NEGERI TERHADAP CITRA IAIN TULUNGAGUNG: Studi Multikasus di Sman I Boyolangu dan MAN Tulungagung 1 - Moh. Nurul Huda (LP2M IAIN Tulungagung, 2016)
The image of an organization will affect public confidence in the organization, so it is important for an organization to build or maintain that image. As an institution of higher education, IAIN Tulungagung made several attempts to create a positive image. Perceptions of students of secondary educational institutions, which is one of the many steakholders that will affect the success of a college course needs special attention. IAIN Tulungagung assumption that emphasizes a balance between religious knowledge and general knowledge, often the pressure point students secondary educational institutions in perceiving IAIN Tulungagung. The dissemination of information is needed to influence the perceptions of students secondary educational institutions against IAIN Tulungagung in the public. The experience and the introduction of the IAIN Tulungagung closer to the community will have positive impact on the image of IAIN Tulungagung. This is so that students have a balanced and factual information quiet IAIN Tulungagung. Teachers, principals, senior, and even the alumni are influential parties in imaging IAIN Tulungagung.Keywords: Perception, Image, IAIN Tulungagung